2018
DOI: 10.1007/s12070-018-1329-0
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Treatment Outcomes of Post Traumatic BPPV in Traumatic Brain Injury Patients

Abstract: The aim of this study is to assess the incidence of post traumatic BPPV and evaluate its treatment outcomes in mild and moderate traumatic head injury patients. The study population consisted of 128 patients (89 male:39 female) who were admitted with head and neck injury (Motor Vehicle Accident, Blow to the head, Fall from Height, Whiplash injury) as inpatients in Department of Neurosurgery in Tertiary care hospital in Kerala during a 2 month period from 1st April 2014 to 31st May 2014. The age range was 10-70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 12 publications
4
21
1
Order By: Relevance
“…This is in accordance with Ahn et al and Davies et al who have reported an incidence of 23% and 25% respectively [5]However, others have documented a lower incidence varying from 8.5% to 17% [7,10,12,13]. The commonest age group affected was 31-50 years group(44.4%) which is in agreement with Jozefowicz Korczynska et al and Haripriya et al [14,13].Males predominated in our cohort(55.6%). Similar observations have been made by others [14,13].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This is in accordance with Ahn et al and Davies et al who have reported an incidence of 23% and 25% respectively [5]However, others have documented a lower incidence varying from 8.5% to 17% [7,10,12,13]. The commonest age group affected was 31-50 years group(44.4%) which is in agreement with Jozefowicz Korczynska et al and Haripriya et al [14,13].Males predominated in our cohort(55.6%). Similar observations have been made by others [14,13].…”
Section: Discussionsupporting
confidence: 93%
“…The commonest age group affected was 31-50 years group(44.4%) which is in agreement with Jozefowicz Korczynska et al and Haripriya et al [14,13].Males predominated in our cohort(55.6%). Similar observations have been made by others [14,13].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations